Investigation of (micro‐)meteoritic materials at the new hard X‐ray imaging PUMA beamline for heritage sciences. (10th October 2019) - Tack, Pieter; Bazi, Benjamin; Vekemans, Bart; Okbinoglu, Tulin; Van Maldeghem, Flore; Goderis, Steven; Schöder, Sebastian; Vincze, Laszlo
Abstract : The PUMA (Photons Utilisés pour les Matériaux Anciens) beamline is made available to scientific communities studying materials from cultural heritage. A detailed analytical characterization of this beamline as an analytical and imaging tool is demonstrated using the Seymchan pallasite meteorite and an Antarctic unmelted micrometeorite as case studies. Abstract : At the French synchrotron facility SOLEIL, a new X‐ray imaging facility PUMA (Photons Utilisés pour les Matériaux Anciens) has been made available to scientific communities studying materials from cultural heritage. This new instrument aims to achieve 2D and 3D imaging with microscopic resolution, applying different analytical techniques including X‐ray fluorescence spectroscopy (XRF), X‐ray absorption spectroscopy (XAS), X‐ray diffraction and phase‐contrast imaging. In order to discover its capabilities a detailed analytical characterization of this beamline as an analytical and imaging tool is deemed necessary. In this work, (confocal) XRF and XAS analyses are demonstrated using the Seymchan pallasite meteorite and an Antarctic unmelted micrometeorite as case studies. The obtained spatial resolution (2 µm × 3 µm) and sensitivity (detection limits <10 p.p.m. for 1 s acquisition at 18 keV) show that PUMA is a competitive state‐of‐the‐art beamline, providing several high‐profile and high‐in‐demand analytical methods while maintaining applicability towards a wide range of heritage‐oriented sciences.